'Possible Selves' in practice: how students at Further Education Colleges in England conceptualise university. Issue 6 (2nd November 2022) - Jones, Steven; Hordósy, Rita; Mittelmeier, Jenna; Quyoum, Aunam; McCaldin, Tamsin
ABSTRACT: This paper reports on a project in the North of England that looks at the college-to-university decision-making processes of non-traditional students through the conceptual lens of 'Possible Selves', as initially developed by Markus and Nurius (1986) and applied to higher education by Harrison (2018), Henderson (2019) and others. Our data involves in-depth interviews with young people, and with the college staff responsible for advising and guiding them, at Further Education Colleges from which the rate of transition to university is lower than the national average. Our findings show that young people talk about their 'like-to-be' and 'like-to-avoid' futures in complex and self-regulated ways, often moderating how they articulate aspiration to align with external discourses, such as those projected by college staff. Students also demonstrate a keen awareness of structural limits, effectively constructing future selves which, though 'elaborated', reflect counter-reading of dominant narratives around financial self-improvement as achieved via the 'full' university experience. The 'Possible Selves' approach is therefore found to be enabling as a mediating artefact for researchers, and valuable for identifying policy-relevant points of tension between students and their college staff.